Detection of Pancreatic Beta Cell Reserve and Its Relationship with Metabolic Markers and Anthropometric Measurements in Patients with Active Psychotic and Mood Disorders - Uslu, Muhammed Fuad; Kilinc, Faruk; Kurt, Osman; Gürok, Mehmet Gürkan; Ustundag, Bilal; Karatepe, Bercem Afsar (My University, 2024)
Objective: In this research, our objective is to explore how pancreatic beta cell reserve is determined and its correlation with metabolic markers among individuals receiving active treatment for psychotic and mood disorders. Materials and Methods: The study included 60 healthy controls and 60 psychiatrically treated patients on regular antipsychotic medication. Insulin, c-peptide, cholesterol, triglyceride, LDL cholesterol, HDL cholesterol, vitamin D, HbA1c, parathormone, prolactin, TSH levels were analyzed after anthropometric measurements of all participants. Results: The Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) value was notably greater in the case group compared to the control group, with a significant difference observed (p=0.041). Triglyceride (TG), Very low density lipoprotein (VLDL), Total cholesterol and Low density lipoprotein (LDL) values of the case group were significantly higher than the control group. During the correlation analysis, a noteworthy positive correlation was identified between weight and BMI, waist circumference, waist-to-neck ratio, waist-to-hip ratio, insulin levels, and c-peptide levels. Conclusion: We believe that individuals with high-risk factors should undergo regular monitoring for conditions such as obesity, insulin resistance, hyperlipidemia, prediabetes, and diabetes, which can be beneficial.
Keywords: Metabolic disorder; Antipsycohotics; pancreatic beta cell